Sistem Pengunci Pintu Otomatis Menggunakan Sensor Fingerprint Berbasis Arduino - Ardian Sumantri; La Ode Ahmad Barata; Salimin (Piston: Jurnal Teknologi, 2022)
The increasing development of science and technology is marked by the rapid progress that occurs with the creation of increasingly sophisticated equipment as well as security systems such as door locks. The design of this tool aims to increase the security of the door and to increase the power of creativity, innovation and expertise. This system uses an Arduino microcontroller board that functions as a control center, a fingerprint sensor is used to open the lock from outside and an ultrasonic sensor is used to open the lock from inside the room, and this system is equipped with a conventional key as an unlocker if a problem occurs in the system. The results of testing this tool on the fingerprint sensor, the test is carried out using five fingers, where three fingers have been registered and two fingers are not registered. Two fingers that have been registered can be read and one finger that has been registered cannot be read, this can occur due to several factors such as dirty sensor fingers, incorrect finger positions and others. In the ultrasonic sensor there is no problem with the sensor. This tool has the advantage that the level of security is higher than conventional keys and has a conventional key as a backup in case of a problem with the system. This tool also has the disadvantage that it must always be connected to a power source, but in the event of a power outage, it can use batteries. Some components of this tool will also heat up if it is continuously connected to a power source but can be overcome by using a heatsink or other type of cooler.